Sonographic features of uterine fibroids that predict the ablation rate and efficacy of high-intensity focused ultrasound - Xue, Hailan; Wu, Songsong; Xiao, Kunhong; Ding, Guisheng; Chen, Sheng (Frontiers in Oncology, 2024)
Objective This study aimed to identify the sonographic indicators that predict the ablation rate and efficiency of uterine fibroids during high-intensity focused ultrasound (HIFU) treatment. Methods In this retrospective study, we analyzed the clinical data of patients with uterine fibroids who underwent HIFU treatment at Fujian Provincial Hospital between April 2019 and April 2022. Routine abdominal ultrasound examinations were performed to observe potential indicators before the HIFU treatment. After the treatment, enhanced magnetic resonance imaging (MRI) examination was performed within 2 weeks. The fibroid and non-perfused volumes (NPV) were determined, and the ablation rate and energy efficiency factor (EEF) were calculated. Results A total of 75 patients (124 uterine fibroids) were included in this study. Uterine fibroids with a larger volume, high echogenicity, elliptical/diffuse leaf shape, and a posterior attenuation band had a higher HIFU ablation rate (p<0.05). Uterine fibroids with a larger volume and high echogenicity and without necrotic areas had a lower EEF (p<0.05). Multiple comparisons between fibroid types revealed statistically significant differences in EEF between subserosal and submucosal fibroids (p < 0.05) and between subserosal and mixed-type fibroids (p < 0.05). However, no statistically significant difference was observed between mixed-type and submucosal fibroids. The HIFU ablation rate and EEF showed no significant differences based on location within the wall and blood flow within the fibroids. Conclusion Sonographic features of uterine fibroids can predict the rate and efficiency of HIFU ablation, providing useful guidance in selecting appropriate treatment for patients.